The Chronic Effects of Narghile Use on Males' Cardiovascular Response During Exercise: A Systematic Review. Issue 2 (March 2021) - Chaieb, Faten; Ben Saad, Helmi
Narghile use has regained popularity throughout the world. Public opinion misjudges its chronic harmful effects on health, especially on the cardiovascular system. This systematic review aimed to evaluate the chronic effects of narghile use on cardiovascular response during exercise. It followed the preferred reporting items for systematic reviews guidelines. Original articles from PubMed and Scopus published until January 31, 2020, written in English, and tackling the chronic effects of narghile use on human cardiovascular response during exercise were considered. Five studies met the inclusion criteria. Only males were included in these studies. They were published between 2014 and 2017 by teams from Tunisia ( n = 4) and Jordan ( n = 1). One study applied the 6-min walk test, and four studies opted for the cardiopulmonary exercise test. Narghile use was associated with reduced submaximal (e.g., lower 6-min walk distance) and maximal aerobic capacities (e.g., lower maximal oxygen uptake) with abnormal cardiovascular status at rest (e.g., increase in heart rate and blood pressures), at the end of the exercise (e.g., lower heart rate, tendency to chronotropic insufficiency) and during the recovery period (e.g., lower recovery index). To conclude, chronic narghile use has negative effects on cardiovascular response to exercise with reduced submaximal and maximal exercise capacities.